A study on the Role of Self-Service Technologies in Enhancing Relationship Marketing in Commercial Banks. - Machado C, Tresena; Annaraj, S Daniel David; Sharma, Rekha; Desai, Juhi Puri; Hanchanale, Ojas Basavaraj; Mugloo, Nasir Gulzar (Journal of Neonatal Surgery, 2025)
The digital era is witnessing a shift in paradigm from service-based economy towards self-service economy. Technology has been proactively penetrating into organisations and plays a crucial role in upgrading the operational efficiency and enhancing user experience. To catch up with the winds of changing times, banks are constantly evolving and expanding their self-service banking solutions. The widespread use of digital payments and mobile/internet banking has made banking services accessible and convenient for customers and has cause a shift in preference towards SST over traditional banking. The challenging factor for banks with SSB is enhancing customer relationships through these channels. The study examines the influence of SST on customer experience, satisfaction, retention and loyalty. Data for the study is collected from 80 respondents across Thoothukudi District through a structured questionnaire. The findings are that all five dimensions of SSB: Accessibility, Security, Reliability, Competence and Control have positive significant relationship with customer experience and customer satisfaction. However, the relationship of these dimensions with customer retention is insignificant